A beginner's guide to understanding and implementing the genetic modification of zebrafish. (October 2018) - Rafferty, Sara A.; Quinn, T. Alexander
Abstract: Zebrafish are a relevant and useful vertebrate model species to study normal- and patho-physiology, including that of the heart, due to conservation of protein-coding genes, organ system organisation and function, and efficient breeding and housing. Their amenability to genetic modification, particularly compared to other vertebrate species, is another great advantage, and is the focus of this review. A vast number of genetically engineered zebrafish lines and methods for their creation exist, but their incorporation into research programs is hindered by the overwhelming amount of technical details. The purpose of this paper is to provide a simplified guide to the fundamental information required by the uninitiated researcher for the thorough understanding, critical evaluation, and effective implementation of genetic approaches in the zebrafish. First, an overview of existing zebrafish lines generated through large scale chemical mutagenesis, retroviral insertional mutagenesis, and gene and enhancer trap screens is presented. Second, descriptions of commonly-used genetic modification methods are provided including Tol2 transposon, TALENs (transcription activator-like effector nucleases), and CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9). Lastly, design features of genetic modification strategies such as promoters, fluorescent reporters, and conditional transgenesis, are summarised. As a comprehensive resource containing both background information and technical notes of how to obtain or generate zebrafish, this review compliments existing resources to facilitate the use of genetically-modified zebrafish by researchers who are new to the field.